Evaluación técnico financiera del servicio de monitoreo real time para bombas electrosumergibles (ESP) en cinco pozos del Campo Casabe (2018)
This degree project develops a brief description of the Casabe oilfield, explaining characteristics about its location, stratigraphy and lithology; following, it does the description of the artificial lift system electrical submersible pump (ESP) in order to determine the impact of the Real Time Surveillance service on five oil wells of the oilfield, using the software DesignPro and LiftIQ, analyzing the benefits of this service in their operation. Finally, a financial evaluation of the project is developed using the VPN methodology.